2007
DOI: 10.1080/00016480601089416
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptors in cultured nasal epithelial cells

Abstract: ALI + RA culture developed ciliary differentiation as observed by light and scanning electron microscopic examination in 3 weeks. It had higher interleukin (IL)-8 basal secretion (21.9 vs 0.82-1.45 ng/ml) and transepithelial potential (-20.4 mV). TLR1-10 mRNA expression in cultured nasal epithelial cells was determined by RT-PCR. Only TLR3 mRNA significantly increased at day 20 vs day 1 (n=5, p=0.02) in ALI + RA cell culture. Higher TLR3 protein was also expressed at day 20 in ALI + RA cell culture but not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
(32 reference statements)
0
30
0
Order By: Relevance
“…Nasal epithelial cells (hNECs) located at mucosal surface serve as the first barrier to microbial challenge and are permissive to drug or vaccine delivery [1], [2]. Epithelial cells are capable of producing various cytokines, chemokines, and growth factors by recognizing microbial-associated molecular patterns (MAMPs) from colonizing microbes or invading pathogens through pathogen recognition receptors, such as Toll-like receptors (TLRs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal epithelial cells (hNECs) located at mucosal surface serve as the first barrier to microbial challenge and are permissive to drug or vaccine delivery [1], [2]. Epithelial cells are capable of producing various cytokines, chemokines, and growth factors by recognizing microbial-associated molecular patterns (MAMPs) from colonizing microbes or invading pathogens through pathogen recognition receptors, such as Toll-like receptors (TLRs).…”
Section: Introductionmentioning
confidence: 99%
“…We have established a system for culturing human primary nasal epithelial cells in vitro to subsequently harvest well-differentiated hNECs, as determined by cililary differentiation [11], which express both TLR2 and TLR4 [2]. We previously demonstrated that immunodominant glycoprotein 60 (IDG60) from oral commensal Streptococcus mutans is an immunodominat antigen that elucidates a relatively high secretory IgA, serum IgG, and memory CD4+ T cell proliferative responses in the general population [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to innate immune cells [8,9] , a number of other cell types express TLR3, including nasal [10] , intestinal [11] and endometrial [12,13] epithelium. Signaling through TLR3 results in downstream activation of proinflammatory genes such as TNF-␣ and IL-12 [14] , which inhibit viral replication [15] and stimulate T cells [16] , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Messenger RNA (mRNA) for all 10 TLRs have been identified in SNECs, and their function has been demonstrated by induced production of innate immune effectors such as human β-defensin 2, serum amyloid A, and surfactant proteins A and D [64]. The activity of SNEC TLRs is abnormally diminished in recalcitrant CRSwNP [6567]. In addition, expression of the antimicrobial protein, lactoferrin, is decreased at the mRNA and protein level in the nasal mucosa of CRS patients [28•, 68].…”
Section: Inflammation Caused By Intrinsic Host Factorsmentioning
confidence: 99%